Needs and Expectations of the Communities Surrounding the Navaminda Kasatriyadhiraj Royal Air Force Academy, Muak Lek District, Saraburi Province - Yingpisutt, Aimmarat; Chotedelok , Anuruk; Udompoth, Sriwan; Sitthiwong, Akkapong (CRMA Journal of Humanities and Social Sciences, 2022)
The aims of this research were to 1) Survey the needs and the expectations of the target communities; and 2) Compare the needs and expectations of the members of the communities, as categorized by their occupations and age groups. The tools used for data collection were questionnaires that was answered by 232 respondents and data from 45 people who participated in the group interview. The statistics used in the data analysis were percentage, mean, standard deviation, and the comparison of pairs’ mean by a Least Significant Difference (LSD) method. The results of the study showed that 1) The general needs of the members of the communities; including fundamental needs, security needs, friendship, and community-belonging needs, and the needs for academic services and job opportunities were at the highest level, where 47.80 percent of respondents had the expectation that these needs will be met successfully; and 2) When comparing the needs and expectations of people in the communities, it was found that people with different occupations did not have differing needs in all aspects. When classified by age groups, it was found that those in the age group over 26 years old had the highest level of fundamental needs. The age group over 40 years old required the greatest needs for friendship and community-belonging. Nevertheless, it found no statistically significant differences in needs for community security, academic services, and job opportunities. Finally, it found no correlation between the expectations of people who had different occupations towards the Navaminda Kasatriyadhiraj Royal Air Force Academy. When classified by age groups, it also found no correlation between the different ages and the expectations of the community.